Magnetic properties of gadolinium and carbon co-doped gallium nitride. (January 2017) - Syed Kaleemullah, N.; Ramsubramanian, S.; Mohankumar, R.; Munawar Basha, S.; Rajagopalan, M.; Kumar, J.
Abstract: Investigations have been carried out to study the ferromagnetic properties of Gadolinium (Gd) Carbon (C) co-doped wurtzite Gallium Nitride (GaN) using full-potential linear augmented plane wave (FP-LAPW) method within the density functional theory. The system shows half-metallic nature when single Gd is substituted in Ga36 N36 supercell. The presence of carbon in GaN supercell is found to generate weak magnetic moment ( M s ) in the neighbouring atoms. When Carbon is codoped in the Gd-GaN, it increased the total magnetic moment of the system ( M tot ). The cause of ferromagnetism in the Gd and C co-doped GaN has been explained by Zener's p-d exchange mechanism. The role of defects in the magnetic property of this system is also investigated. The results indicate the gallium vacancy influences the magnetic moment of the Gd and C codoped GaN more than the nitrogen vacancy. The presence of holes is effective than electrons in achieving the ferromagnetism in the considered system. Highlights: The system shows half metallic character when Gd is doped in GaN supercell. With the introduction of Carbon in GaN the system turns metallic. The spin magnetic moment of Gd and C in GaN system is different for different positions. Total magnetic moment of the system is not affected much by N vacancy but by Ga vacancy.